Managing Strategic Change in a Mature Business - Pettigrew, A; Whipp, R; Rosenfeld, R (1989)
The article draws on the experience of four sectors of the U.K. economy to suggest what the competetive conditions of the next decade might look like. The distinction is made between barries to entry and barries to success. Strategic management in the more successful companies appears to involve the common ability to sustain strategic flexibility. The majority of the piece indicates how this quality has been fashioned and how the process of its creation and maintenance has been managed in the companies concerned. Evidence from the four sectors is used to speculate on some of the key determinants of strategic flexibility in the 1990s.